Effect of airway clearance techniques in patients experiencing an acute exacerbation of bronchiectasis: a systematic review. (1st December 2020) - Phillips, Jennifer; Lee, Annemarie; Pope, Rodney; Hing, Wayne
ABSTRACT: Background : Airway clearance techniques (ACTs) are recommended for people with bronchiectasis both in stable state and during an acute exacerbation. Research has previously investigated ACTs for individuals in a stable state, but the safety and efficacy of ACTs during an acute exacerbation has not been reviewed. Methods : A systematic review was completed for studies of ACTs undertaken in adults and children experiencing an acute exacerbation of bronchiectasis. The databases Pubmed, Embase, PEDro, and CINAHL were searched. Methodological quality of studies was examined using the modified Downs and Black tool. Key findings were synthesized using a critical narrative approach. Results : Six studies were included with a total of 120 participants. No eligible studies involving child participants were found. Overall, the methodological quality of studies was moderate. All ACTs investigated appeared safe for adults, with no adverse reactions reported. The active cycle of breathing technique may be more effective at improving gas exchange, sputum volume, and health-related quality of life compared to postural drainage and percussion. Participants in two studies preferred oscillating positive expiratory pressure devices over the active cycle of breathing or postural drainage techniques. Conclusions : All ACTs reported in this review appeared safe for adults experiencing an acute exacerbation of bronchiectasis.